The Implementation of Class Action Research (CAR) by Japanese Language Teachers in Indonesia - Haristiani, Nuria; Rizki Oktarina, Diana (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2021)
This study aims to determine the implementation of Classroom Action Research (CAR) conducted by Japanese language teachers in Indonesia at this time. A qualitative descriptive research method was used in this study to describe the questionnaire result from 193 participants in the first session of webinar, and 203 participants in the second session. Based on the results of the questionnaire, it was found that most of the participants had never done CAR at all or had never done CAR in a structured manner. Participants who have done CAR mostly use it for promotion and only a small number use it for teaching development. This research cannot represent the overall field conditions but is expected to provide an overview of the current CAR implementation by Japanese language teachers in Indonesia, and the development of teaching materials that can be developed through routine CAR.